The Evolving Landscape of Immunotherapy in Uterine Cancer: A Comprehensive Review - Bashar Haj Hamoud; Romina Marina Sima; Ileana Adela Vacaroiu; Mihai-Teodor Georgescu; Anca Bobirca; Alexandra Gaube; Florin Bobirca; Dragos-Eugen Georgescu (Life, 2023)
Endometrial cancer affects the uterus and is becoming increasingly common and deadly. Although surgery and adjuvant pelvic radiotherapy can often cure the disease when it is contained in the uterus, patients with metastatic or recurrent disease have limited response rates to chemotherapy, targeted agents, and hormonal therapy. To address this unmet clinical need, innovative treatment strategies are needed, and a growing focus on the immunomodulation of the tumor microenvironment has arisen. Current data suggest that active and/or passive immunotherapy may be promising for the treatment of endometrial cancer.